The importance of multi-professional, interdisciplinary care in rehabilitation and health promotion directed at patients with cleft lip/palate - Lorenzzoni, Daniela (2010)
Cleft lip/palate is the one of the most prevalent congenital craniofacial deformities. According to data from the Brazilian Institute of Statistics and studies carried out at the Craniofacial Anomaly Rehabilitation Hospital in Bauru/SP, cleft lip/palate occurs in one out of every 650 births in Brazil. Cleft lip/palate may result in impairments that stigmatize the individual and have an impact on health, emotions and social interaction. Treatment requires children with cleft lip/palate to be monitored from birth to young adulthood in order to avoid further functional, aesthetic and psychological impact. The present literature review offers reflections on the organization of the work process of multi-professional, interdisciplinary care in rehabilitation and health promotion directed at patients with cleft lip/palate. There are gaps in the integration between the specialties that make up the three levels of care in the Brazilian public health care system and there is a need for the government to ensure reference and counter-reference services.